Eastern Caribbean Central Bank : Report on Observance of Standards and Codes; Data Module, Response by the Authorities, and Detailed Assessment Using the Data Quality Assessment Framework (DQAF). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This report focuses on the Monetary Statistics Component of the Regional Data Module Report on the Observance of Standards and Codes for the Eastern Caribbean Central Bank (ECCB). The report reveals that with respect to the prerequisites of quality and assurances of integrity, the legislation broadly supports mandatory data reporting and the confidentiality of the reported data. However, the ECCB's responsibility for compiling and disseminating monetary statistics to the public is not clearly specified in the law. Regarding resources, the number of staff allocated to the compilation of monetary statistics is inadequate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet